Analisis Kebutuhan untuk Pengembangan Bahan Ajar Berbentuk Komik Manga pada Materi Jaringan Hewan Kelas XI SMA - Ummul Barokahhuda; Ramadhan Sumarmin; Helendra Helendra; Relsas Yogica (Jurusan Pendidikan Biologi - Universitas Siliwangi, 2021)
Students' understanding of the material and students' interest in learning can be improved in various ways, one of which is using teaching materials in the form of comics. Students tend to like things that match their preferences, including the teaching materials used in learning. This study aims to determine students' preferences for the types of comics developed as teaching materials for animal tissue material for 11th grade Senior High School. The descriptive quantitative approach is the method used in this study with all students of class 11th grade MIPA SMAN 1 Padang Panjang. The sample was randomly selected as much as 10% of the students in each class using the probability sampling-random sampling technique. The instruments used to collect research data are interview sheets by teachers and needs analysis questionnaires by students. The needs analysis questionnaire, curriculum analysis, analysis of teaching materials and analysis of students are carried out. This study indicates that students need alternative teaching materials in the form of comics and are familiar and tend to like Japanese-style comics or manga comics. Based on the results of this study, it is necessary to develop teaching materials in the form of manga comics on animal tissue material for 11th grade SMA.